Pengaruh Yang Signifikan Antara Penggunaan Media Audio Visual Berbasis Teknologi (Canva) Terhadap Motivasi Belajar Peserta Didik Pada Mata Pelajaran Sejarah Kebudayaan Islam Kelas VIII Di MTS Assiraj Kab. Bekasi - Rachmat Fahriza Nugrahai; Oyoh Bariah; Farida Nur Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the effect of using Canva-based audiovisual media on the learning motivation of eighth-grade students at MTs Assiraj. This study employed a correlational research method and was conducted at MTs Assiraj, Bekasi Regency. The study population consisted of a single eighth-grade class comprising 39 to 47 students. A saturated sampling technique was used. Data collection was carried out using questionnaires, and data analysis was performed using the t-test. The hypothesis testing results showed a Sig. (2-tailed) value of 0.000, which is less than the significance level (α) of 0.05; thus, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Consequently, it can be concluded that the use of Canva influences students' learning motivation.